Pengaruh Beban Kerja Terhadap Produktifitas Kerja Di Unit Pelaksana Teknis Rumah Sakit Pratama Kota Yogyakarta - Suliantoro Suliantoro (Jurnal Bisnis, Manajemen, dan Akuntansi, 2021)
The purpose of this study was to examine the effect of workload on work productivity of non-health worker employees. There is an organization in management workload is into two, namely workload and high workload. Workload are some or a series of activities must be completed by an organization or holder of a within a certain period. Give the workloads effective organization can be aware of the extent to which employees can be given maximum workload and the extent to which its effect on productivity employee performance. It self Productivity were their mental attitude that melatar such employees to produce a better performance than yesterday. Productivity in the the last result obtained in a process. Increased productivity, can be achieved if the employee could understand exactly about factor increasing work productivity. Success Organization that employees can work well, and having high productivity to achieve the goals of the organization itself. In this research, the use writers the quantitative methods. After they won an minutely so the authors found , there are real impact between the workloads against work productivity in the hospital pratama the city of yogyakarta .